The effects of cooling via compressed air on geometrical, mechanical and microstructural properties of 600 MPa high strength steel walls manufactured by CMT WAAM - Mert, Tolga; Tumer, Mustafa (SPRINGER HEIDELBERG, 2026)
In this study, the effects of compressed air cooling (CAC) and free cooling (FC) applied between the layers of the walls fabricated by cold metal transfer wire arc additive manufacturing (CMT-WAAM) process on the microstructural changes and the effects of these changes on the mechanical properties using high strength (minimum 600 MPa) steel wire were investigated. Neither shielding gas nor special tooling was utilized. Compressed air gun in the workshop was used to supply compressed air. The wall obtained with FC was wider (21%) and higher (7%), while the average sidewall roughness (waviness) values were 128% higher than the CACed wall. The results showed that the cooling rate had a decisive influence on the microstructure; CAC promoted the formation of lower bainite and martensite/austenite (M/A) phases, leading to a significant increase in strength values. On the other hand, FC led to the formation of upper bainite and increased inclusion density, which partially negatively affected the mechanical strength. CAC resulted in a 124% and 47% increase in average yield and tensile strength, respectively. The CACed WAAM walls showed higher hardness values in all regions compared to the FCed ones, especially in the upper wall region, where the hardness was measured to be 288 +/- 14 HV0.2 compared to 171 +/- 7 HV0.2 for the FCed wall. Notch impact tests at - 20 degrees C and - 50 degrees C revealed a 17.5% and 10.8% reduction in toughness of the CACed walls compared to the FCed walls, respectively, but the ductile fracture behavior was maintained in both cases.
Keywords: High strength steel; CMT-WAAM; Compressed air cooling; Microstructure; Strength; Side wall surface waviness; Metallurgy & Metallurgical Engineering